Предмет: Алгебра, автор: lentbs228

Помогите пожалуйста!!!​

Приложения:

Ответы

Автор ответа: xurshedxon23
0

Ответ:

 \frac{ {a}^{ - 5}( {a}^{2} {)}^{8}   }{ {a}^{20}( {a}^{ - 2} {)}^{3}   }  =  \frac{ {a}^{ - 5} \times  {a}^{16}  }{ {a}^{20} \times  {a}^{ - 6}  }  =  \frac{ {a}^{ - 5 + 16} }{ {a}^{20 - 6} }  =  \frac{ {a}^{11} }{ {a}^{14} }  =  {a}^{11 - 14}  =  {a}^{ - 3}  \\ ( {3}^{ - 1} {)}^{ - 3}  =  {3}^{ - 1 \times ( - 3)}  =  {3}^{3}  = 27

Похожие вопросы
Предмет: Литература, автор: mnagornyj25
Предмет: Алгебра, автор: aleksejpanin2000